Whole genome characterization of Streptococcus pneumoniae from respiratory and blood cultures collected from Canadian hospitals before and after PCV-13 implementation in Canada: Focus on serotypes 22F and 33F from CANWARD 2007–2018. Issue 39 (15th September 2021) - Golden, Alyssa R.; Adam, Heather J.; Baxter, Melanie; Martin, Irene; Demczuk, Walter; Mulvey, Michael R.; Karlowsky, James A.; Zhanel, George G.; ,
Abstract: The population of pneumococci circulating in Canada is constantly shifting under the pressures of antimicrobial and conjugate vaccine use. A new 15-valent pneumococcal conjugate vaccine (PCV), containing PCV-13 serotypes plus additional serotypes 22F and 33F, is currently undergoing clinical trials. The purpose of this study was to utilize whole genome sequencing to characterize invasive and respiratory Streptococcus pneumoniae isolates collected from Canadian hospitals pre- (2007–2011) and post-PCV-13 implementation (2012–2018) in Canada, particularly serotypes 22F and 33F. Isolates were obtained from the CANWARD 2007 to 2018 study. Overall, 597 S. pneumoniae isolates were sequenced using the Illumina MiSeq platform: 180 (101 respiratory, 79 blood) isolates of serotype 22F, 74 (41 respiratory, 33 blood) isolates of serotype 33F and 343 isolates randomly selected to broadly encompass pneumococci in Canada. Genomes were clustered using PopPUNK v2.0.2 and assigned to a Global Pneumococcal Sequencing Cluster (GPSC) and MLST sequence type (ST), and visualized using Cytoscape v3.8.0. Acquired resistance genes were identified using ResFinder 2.1, and genes with chromosomal mutations conferring resistance were extracted and compared to standard reference genome R6. PopPUNK clustering suggests that a clone of S. pneumoniae serotype 22F/ST433/GPSC19 demonstrating mefA -mediated macrolide resistance is emerging in Canada post-PCV-13 introduction, collected from both invasive and respiratory sources. Similarly, there is evidence to support a post-PCV-13 shift towards macrolide- and trimethoprim/sulfamethoxazole-resistant serotype 33F/ST100/GPSC3, including a cluster associated with invasive isolates. While some lineages containing vaccine serotypes were predominantly identified pre-PCV-13 implementation (serotype 5/GPSC8, serotype 7F/GPSC15), others (serotype 19A/GPSC1 and 4, serotype 3/GPSC12) continue to maintain a significant presence over time despite inclusion in PCV-13. Further genomic surveillance is necessary to determine additional trends over time in these upcoming vaccine serotypes, as well as the overall pneumococcal population in Canada.